Does shooting rhythm have an influence upon shooting accuracy in biathlon? - Milje, H.; Brouner, J. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: Nitzsche (1998, cited in Sattlecker er a/., 2007) stated that Shooting Rhythm is a key influence upon Shooting Accuracy in biathlon, with Augustin and Moravec`s (2002) further support this statement. With these researchers examining shooting in a controlled environment, the influence of Shooting Rhythm has never been investigated in a competition setting. Investigating the influence of Shooting Rhythm during competition would increase the depth of knowledge within this area. Analysing shooting during competition in biathlon is also seen as the ideal method, as all influencing variables would be present (Sattlecker er a/., 2007). The purpose of this study was to investigate whether Shooting Rhythm have an influence upon Shooting Accuracy in elite biathlon competition. Methods: 104 elite male biathletes competing in the Individual 20km in Oestersund during the 2015/16 Biathlon World Cup were used for the study. Hand-based notational analysis was utilised for the study. In order to assess the Shooting Rhythm of the biathletes, a system was specifically designed for this study. The influence of Shooting Rhythm upon Shooting Accuracy would be analysed using the Spearman`s Correlations test. The KPIs can be seen in Table 1. The shooting is performed in two positions, prone and standing, and the correlation will also be calculated for each position. Results: The correlation between Shooting Rhythm and Shooting Accuracy was 0.516. For prone shooting the correlation was 0.506 and for standing shooting the correlation was 0.502. This indicates a direct moderate correlation between Shooting Rhythm and Shooting Accuracy. The correlation between Shooting Rhythm and Shooting Accuracy was statistically significant with P<0.01. Conclusion: The results of this study indicate that Shooting Rhythm has a positive influence upon Shooting Accuracy in biathlon. It would therefore be beneficial for biathletes to shoot with a "good" Shooting Rhythm in order to achieve the desired shooting result. Further research should consider investigating the influence of Shooting Rhythm over a whole season and for all the various race types in biathlon. Research should also look to establish an optimal rhythm in biathlon to enhance accuracy and be as time efficient as possible across the two shooting positions.